An 8-year follow-up of resin infiltration on anterior white spot lesions - Omoto, Érika M [UNESP]; Oliveira, Laryssa C. [UNESP]; Rocha, Rafael S. [UNESP]; Machado, Lucas Silveira; Bresciani, Eduardo [UNESP]; Prakki, Anuradha; Fagundes, Ticiane Cestari [UNESP] (Wolters Kluwer, 2023)
White spot lesions (WSLs) are sites of enamel surface and subsurface demineralization that increases tissue porosity and affects the teeth appearance. The resin infiltration technique proved to be a valid alternative to arrest caries lesion progression and to masking a color change in noncavitated WSLs. Thus, this study aims to report a clinical case of anterior WSLs treated with resin infiltration technique with an 8-year follow-up. The resin infiltration protocol was performed in an 18-year-old female patient presenting WSLs on the maxillary right lateral incisor, left central incisor, and left canine. The protocol followed the manufacturer's recommendations. The patient reported satisfaction with the smile appearance, at the end of the appointment. Infiltrated areas remained unchanged after an 8-year follow-up, showing an acceptable result for the patient's esthetic desires. After 8 years of evaluation, the resin infiltration technique proved to be a resistant and reliable alternative in preventing caries progression and in color masking WSLs.
Keywords: case report; dental caries; dental enamel; Esthetics; resin infiltrant